2009
DOI: 10.1002/path.2603
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma originates from mesenchymal stem cells in consequence of aneuploidization and genomic loss of Cdkn2

Abstract: High-grade osteosarcoma is characterized by extensive genetic instability, thereby hampering the identification of causative gene mutations and understanding of the underlying pathological processes. It lacks a benign precursor lesion and reports on associations with hereditary predisposition or germline mutations are uncommon, despite the early age of onset. Here we demonstrate a novel comprehensive approach for the study of premalignant stages of osteosarcoma development in a murine mesenchymal stem cell (MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
207
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(226 citation statements)
references
References 41 publications
6
207
2
1
Order By: Relevance
“…(17) A separate line of evidence comes from the observation that serially passaged murine mesenchymal stem cells will undergo rare spontaneous transformation resulting in an osteosarcoma-like tumor, suggesting that these cells are the cell of origin. (18,19) With the existing available data, it is not possible to define whether osteosarcoma derives from mesenchymal stem cells or a more differentiated progenitor. The rarity of osteosarcoma may be related to a small pool of cells being capable of producing the cancer.…”
Section: Etiology Of Osteosarcomamentioning
confidence: 99%
See 2 more Smart Citations
“…(17) A separate line of evidence comes from the observation that serially passaged murine mesenchymal stem cells will undergo rare spontaneous transformation resulting in an osteosarcoma-like tumor, suggesting that these cells are the cell of origin. (18,19) With the existing available data, it is not possible to define whether osteosarcoma derives from mesenchymal stem cells or a more differentiated progenitor. The rarity of osteosarcoma may be related to a small pool of cells being capable of producing the cancer.…”
Section: Etiology Of Osteosarcomamentioning
confidence: 99%
“…The aforementioned observation of spontaneous transformation of murine mesenchymal cells into osteosarcoma has been used to study pathogenesis. (18) A parallel and functional phenotypic analysis of the parental mesenchymal stem cells, transformed mesenchymal stem cells, and resulting osteosarcoma suggested aneuploidization, translocations, and homozygous loss of the cdkn2 region as the major mediators of malignant transformation. (18) This same research group has performed expression profiling of these cell types and has suggested that downregulation of Wnt signaling has an important role in osteosarcoma pathogenesis.…”
Section: Etiology Of Osteosarcomamentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse MSCs Mouse MSCs (mMSCs) are especially predisposed to acquiring transformation events after long-term in vitro culture favoring clonal selection of transformed cells [15][16][17][18][19] (Table 1). Upon inoculation into immunodeficient mice, spontaneously transformed mMSCs promote the formation of sarcomas resembling the histopathological properties of fibrosarcoma [15,16] and osteosarcoma [17,18].…”
Section: Spontaneous Transformation Of Mscsmentioning
confidence: 99%
“…34,35 Moreover, inactivation of CDKN2A is associated with a more aggressive behavior in many cancers, including for instance Ewing sarcoma 34,36,37 and osteosarcoma. 38,39 Here, we demonstrate that also patients with angiosarcoma of bone showing loss of Signaling pathways in angiosarcomas expression of CDKN2A have a significantly worse prognosis. To date, few studies have reported the possible role of CDKN2A and TP53 in tumor development in a subset of angiosarcomas of soft tissue.…”
Section: Discussionmentioning
confidence: 56%